2001
DOI: 10.1021/ma0015830
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of New Photoresponsive Polyesters Containing Donor−Acceptor Norbornadiene (D−A NBD) Residues by the Polyaddition of D−A NBD Dicarboxylic Acids with Bis(epoxide)s and Their Photochemical Properties

Abstract: Polyesters containing donor-acceptor norbornadiene (D-A NBD) residues in the main chain were synthesized by the polyaddition of D-A NBD dicarboxylic acids, 5-(4-methoxyphenyl)-1,4,6,7,7pentamethyl-2,5-norbornadiene-2,3-dicarboxylic acid and 5,6-bis(4-methoxyphenyl)-7,7-dimethyl-2,5norbornadiene-2,3-dicarboxylic acid, with bis(epoxide)s. The photoisomerization of the NBD residues in the resulting polyesters proceeded smoothly to give the corresponding quadricyclane (QC) groups. The NBD residues in these polyest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
25
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 16 publications
3
25
0
Order By: Relevance
“…As shown in Figure 4 for polymer P1b, the absorption maximum at 278 nm decreases gradually on irradiation indicating a good conversion of the NBD into QC after 20 min. In addition, and as it is reported in the literature,19, 21, 31, 32 an isosbestic point at 228 nm was observed. This phenomenon, which was observed for all the samples means that the photochemical valence isomerization of the NBD units of polymer chains to the corresponding QC groups occurred selectively without side reactions.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…As shown in Figure 4 for polymer P1b, the absorption maximum at 278 nm decreases gradually on irradiation indicating a good conversion of the NBD into QC after 20 min. In addition, and as it is reported in the literature,19, 21, 31, 32 an isosbestic point at 228 nm was observed. This phenomenon, which was observed for all the samples means that the photochemical valence isomerization of the NBD units of polymer chains to the corresponding QC groups occurred selectively without side reactions.…”
Section: Resultssupporting
confidence: 86%
“…Because the experiences were performed with very thin polymer films, it was assumed that the Beer Lambert's law was applicable. So, in this study, this relation was used according to the work published in the literature 18, 20, 31, 33…”
Section: Resultsmentioning
confidence: 99%
“…Molecular Solar Thermal (MOST) technology utilises energy from the sun to convert photoswitchable molecules into a higher energy structure, with the energy able to be stored for prolonged periods . MOST has been represented by several organic based T‐type photochromic molecular motifs such as azobenzene 1 , dihydroazulene 2 , tetracarbonyl‐dirutheniumdifulvalene 3 , and the norbornadiene‐quadricyclane couple ( NBD4‐QC4 ) (Figure ) . T‐type photoswitches are interconvertible between two states, where a light‐driven reaction forms a metastable photo‐isomer that can be thermally returned to the photoactive parent molecule .…”
Section: Introductionmentioning
confidence: 99%
“…21,22 Furthermore, Nishikubo et al [23][24][25][26] synthesized the polymers containing D-A NBD moieties in the main chain or side chain and examined their photo-chemical valence isomerization. It was found that their synthesized polymers had high photochemical reactivities and good fatigues of resistance.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that their synthesized polymers had high photochemical reactivities and good fatigues of resistance. [23][24][25][26] Furthermore, it is expected that the thermal storage energies of the polymers increase with increasing the ratio of the NBD moieties.From these backgrounds, in this article, we examined the synthesis of the polymers containing D-A NBD moieties in the both main and side chains. The polyesters with D-A moieties in the main chain were obtained by the polyaddition of the bisepoxides with NBD groups and carboxylic dichlorides.…”
mentioning
confidence: 99%